2015
DOI: 10.1007/s11306-015-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive associations between serum fatty acids and lipoproteins in healthy non-obese Norwegians: implications for cardiovascular health

Abstract: A battery of methods for multivariate data analysis has been used to assess the associations between concentrations of fatty acids (FAs) and lipoprotein subclasses and particle size in serum for a normolipidemic population of ethnic Norwegians living in the rural Fjord region. Significant gender differences were found in the lipoprotein and FA patterns. Predictive FA patterns were revealed for lipoprotein features of importance for cardiovascular (CV) health. Thus, the subclasses of atherogenic small and very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 39 publications
2
37
1
Order By: Relevance
“…All samples were taken in the morning after overnight fasting. Serum was obtained according to a standardized protocol (17) and stored at −80 C.…”
Section: Blood Sampling and Measurement Of Fatty Acid Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were taken in the morning after overnight fasting. Serum was obtained according to a standardized protocol (17) and stored at −80 C.…”
Section: Blood Sampling and Measurement Of Fatty Acid Profilesmentioning
confidence: 99%
“…The serum samples were prepared and analysed by minor modifications of the procedure described in Lin et al (17). Total amounts of 18 FAs in each sample were quantified as μg per gram sample.…”
Section: Blood Sampling and Measurement Of Fatty Acid Profilesmentioning
confidence: 99%
“…23, 24 A low EPA/AA ratio is reported to be associated with an increased risk for CVD. 25 The JELIS reported that Epadel reduced cardiovascular events in the Japanese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected between 8 and 10 am after overnight fasting for 1057 ten‐year‐old Norwegian children recruited in the rural Fjord region of Western Norway. Serum was obtained according to the standardized protocol described in Lin et al, split into 0.5 mL aliquots, and stored in cryo tubes at −80°C. At this temperature, the lipoproteins are stable for several years .…”
Section: Methodsmentioning
confidence: 99%